Genotyping by Random Amplified Polymorphic DNA Assay of Acinetobacter baumannii Isolated from Blood Culture of Patients with Hematological Malignancies - S. A. Khrulnova; A. V. Fedorova; I. N. Frolova; G. A. Klyasova (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. Acinetobacter baumannii is a significant nosocomial pathogen that can cause severe infections, especially in immunocompromised patients. Aims. This study aimed to investigate clonal diversity of A. baumannii isolated from blood culture in hematological patients by random amplified polymorphic DNA assay (RAPD). Materials & Methods. Genotyping of A.baumannii isolated from blood culture in hematological patients in 7 Russian hospitals (2003–2017) was assessed by RAPD-PCR with primer OPA-2 (5’-TGCCGAGCTG-3’). The computer-assisted analysis was performed by using GelJ software by UPGMA method and Dice similarity coefficient for banding patterns comparison. Using a similarity coefficient (SC) of ≥ 65%, the strains were grouped. Based on the similarity coefficient, the strains were determined as genetically related (≥ 80%). Strains had identical RAPD-patterns if the similarity coefficient was 100%. Results. A total of 96 A. baumannii strains were examined, of those 77 (80.2%) were nonsusceptible to carbapenems. Acquired OXA-carbapenemase genes were detected among 79.2% carbapenem non-susceptible strains. RAPD-PCR genotyping revealed 84 RAPD patterns. The four groups (A-D) including 98% strains were defined by similarity coefficient ≥65%. The predominant group A included 58 (60.4%) strains, the C and B groups – had 15 strains (15.6%) each, and the group D – 6 strains (6.3%). A total of 82 (85.4%) genetically related A. baumannii with a similarity coefficient ≥ of 80% were allocated into 20 clusters. Identical RAPD-patterns were defined for 22 strains that belonged to 6 clusters within the group A and 1 cluster within the group B. Strains with identical RAPD-patterns were detected in a single hospital as well as in several hospitals located in different cities. Conclusions. The current study has demonstrated genetic diversity and clonal dissemination of A. baumannii in hematological departments.